A Comparative Clinical Study to Evaluate the Effect of Pathyadi Churna and Shunthyadi Kwatha in the Management of Amavata w.s.r to Rheumatoid Arthritis (AYUSHDHARA, 2023)
Amavata is a Vata and Kapha Pradhana Vyadhi caused due to Viruddha Ahara and Vihara resulting in Mandagni, leading to the formation of Ama. Ama with the influence of Vata Dosha circulates all over the body and gets lodged in Shleshma Sthana in Sandhi Pradesha, resulting in the manifestation of Amavata. This Amavata can be compared with rheumatoid arthritis showing similarities in clinical features. Clinically diagnosed 34 patients of Amavata were selected from OPD & IPD of R.G.G.P.G. Ayurvedic College and Hospital Paprola, Dist. Kangra (H.P.). This article discusses the comparative effect of Pathyadi Churna in Group-A and Shunthyadi Kwatha in group-B having 17 patients in each group, in the treatment of Aamvata, mentioned in Chakradatta. It was observed that group of patients treated with Shunthyadi Kwatha (Group-B) showed better result than those patients treated with Pathyadi Churna (Group-A).